"Golden forests" of the sea: assessing values and perceptions of kelp in the Western Cape region of South Africa - Mehta, Akshata (Department of Environmental and Geographical Science, 2022)
Kelp are large seaweeds that provide a variety of contributions to humans and the environment. In South Africa, kelps forests are expanding as a consequence of climate change. In light of this expansion, assessing perceptions and values around kelp may contribute to the implementation of successful marine resource management initiatives. The lack of consideration of non-market values is a gap in kelp valuation studies with kelp ecosystems and their use rarely valued outside of classical economic valuation frameworks. This study aims to fill this research gap, with the intention to elicit perceptions about other value dimensions related to kelp. The study investigates the attitudes and perceptions of value of three groups of actors' (Recreational Users and/or Coastal Community Members, Environmental Managers and Conservationists, and Kelp and/or Abalone Industry Actors) towards kelp in the Western Cape region of South Africa. This is done using the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services' (IPBES) conceptual framework, that considers: (i) kelp as a facet of nature, and (ii) kelp's contributions to people as foci of value that contribute to quality of life. The results of the study indicate that the perceived value of kelp extends far beyond its economic value as a harvested resource. Rather, actors highly value kelp's ecological and social contributions, and have strong relational values towards kelp, recognizing its role in enhancing their quality of life and well-being. Areas of dissonances in valuing kelp's contributions — such as differences in perceptions around kelp's ability to increase one's safety from extreme natural events, or its importance as a source of food and feed for domestic animals — are attributed to individuals' held values as well as their socio-demographic characteristics and situational contexts. While actors did not display significant negative perceptions around kelp, Kelp and/or Abalone Industry Actors indicated frustrations with kelp management strategies and kelp concession permit allocation processes. In turn, 27% of Kelp and/or Abalone Industry Actors perceived inequality in the kelp sector, contributing to a reduction in their appreciation of kelp. The dissertation makes a case for integrated marine resource management solutions aimed towards just and sustainable futures through the recognition of the plurality and complexity of values around kelp. A critique of the IPBES conceptual framework as a methodology is also included, suggesting that its utility is dependent on the objectives of its application. It is recommended that NCP should be considered within the context of governance and access dimensions to elicit a holistic view on assigned values and perceptions towards nature.